﻿ECOS NO VALE DO CHOPIM: MEMÓRIAS E PERTENCIMENTO DE ATINGIDOS POR BARRAGENS EM NOSSA SENHORA DOS NAVEGANTES, PARANÁ - Pocai Filho, Roberto Luiz (2016)
In 1999, a leak of ANEEL information enabled the Movimento dos Atingidos por Barranges (MAB) from accessing the first information about two hydroelectric plants in Chopim Valley that would be built. This work is intended to analyze the different interpretations of the future event in the community Nossa Senhora dos Navegantes in Clevelândia - PR. Gerdau company build dams bothered to create relationships with families affected in order to convince them of their need and its importance. At the heart of the issues of the struggle for land, militants formed with MAB to claim fair compensation. In the context of knowledge and practices, feelings of belonging and different relationship with time the dams allow analyze how affected reinterpret theirexperience of space and appear as its horizon of expectation.